Pengaturan Sistem Manajemen Kesehatan dalam Mewujudkan Kesehatan Masyarakat : Studi terhadap Manajemen Kesehatan di Rumah Sakit Umum Daerah dr. Hendrikus Fernandez Kabupaten Flores Timur - Maria Shevilla Putri Dewa; Kotan Yohanes Stefanus; Yohanes G. Tuba Helan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze the Regulation of the Health Management System in Realizing Public Health at the dr. Hendrikus Fernandez Regional General Hospital, East Flores Regency. This research is a normative juridical research using secondary data consisting of primary legal materials and secondary legal materials collected through literature research in the form of books, laws, legal journals, research-related articles and several from internet sites and other reading sources. The collected legal materials are analyzed qualitatively juridically using a conceptual approach (Conceptual Approach) and a statutory approach (Statute Approach) based on laws that are relevant to theories, legal concepts and principles of problems. The results of this study show that: (1) From the aspect of health management regulation, the lack of support for health management which is the influence of performance is not good. (2) From the aspect that is a factor that hinders the service, the poor arrangement makes the service not good so that there is a lack of satisfaction from the community.